Smoking Behaviour among Secondary School Students in Malaysia - Lukman@Zawawi, Mohamad; Normala, Riza; Azlini, Chik (2018)
The purpose of this study was to scrutinize the smoking behaviours among high school students around Kuala Nerus Terengganu. The two main objectives were 1) smoking behaviours among students and 2) smoking habits among students. This study was conducted involving 419 secondary school students around the Kuala Nerus district in Terengganu, Malaysia. Respondents of this study are limited to students who are smoked only. This study was adopting descriptive analysis approach by using questionnaire as a research instrument. The overall study found that there are various behaviours and smoking habits that influenced secondary school students. The results showed that peers and sex influence were the biggest contributor to the smoking behaviour of students and individuals who had a lot of smokers who influenced smoking habits of school students.